Experimenting urban living lab methodology on circular economy co-design activities in some Italian urban territories - Innella, Carolina; Barberio, Grazia; Brunori, Claudia; Cappellaro, Francesca; Ceddia, Anna Rita; Civita, Rocco; Dimatteo, Salvatore; Ferraris, Marco; Pentassuglia, Rocco; Sciubba, Luigi (Frontiers in Sustainable Cities, 2024)
The Urban Living Lab (ULL) is both a methodology and a place where different actors of a territory can collaborate with the aim of urban transformation and sustainable development. This paper briefly introduces a methodological framework, that combines stakeholder engagement and co-design process on Circular Economy (CE) ideas and projects. The structure of the methodological framework foresees four main phases: scouting and analysis of the territorial context, listening and exploration, participation and execution. The main objective of this paper focuses on the application and experimentation of the same ULL methodology framework in four different Italian urban territories (Anguillara Sabazia in the metropolitan area of Rome, Bologna, Taranto and Venosa, a small town in southern Italy), to highlight how the ULL is an effective approach for stakeholder engagement and co-design processes aiming to the transition toward CE. The discussion section of the four ULL cases highlights the main results of the co-design process: the ideation of project proposals of CE activities suitable for implementation in the reference urban territories. The four ULL cases have shown how the same methodological steps can be applied in urban areas with different geographical, territorial and socio-economic characteristics, with comparable results in terms of activating processes of engagement and co-design within the communities living there. In conclusion, experimenting the proposed methodological framework in each of the four urban areas, despite their differing characteristics, it has stimulated the growth of cultural capital and community ties. This was achieved through the exchange of different skills and the collaborative contributions of multidisciplinary teams, resulting in increased collective awareness.